2017
DOI: 10.1080/00981389.2017.1371100
|View full text |Cite
|
Sign up to set email alerts
|

Self-care among healthcare social workers: An exploratory study

Abstract: Despite growing interest in self-care, few studies have explicitly examined the self-care practices of healthcare social workers. This exploratory study investigated self-care among practitioners (N = 138) in one southeastern state. Overall, data suggest that healthcare social workers only moderately engaged in self-care. Additionally, analyses revealed significant differences in self-care practices by financial stability, overall health, and licensure status, respectively. Interestingly, perceived health stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Given existing, albeit limited, research in this area, perhaps these findings are not surprising. Both Bloomquist et al (2015) and Miller et al (2017) concluded that social workers in their study engaged in self-care moderately. The lack of self-care practices may be associated with contextual factors.…”
Section: Rq1: How Often Do Participants Engage In Self-care Practices?mentioning
confidence: 99%
See 2 more Smart Citations
“…Given existing, albeit limited, research in this area, perhaps these findings are not surprising. Both Bloomquist et al (2015) and Miller et al (2017) concluded that social workers in their study engaged in self-care moderately. The lack of self-care practices may be associated with contextual factors.…”
Section: Rq1: How Often Do Participants Engage In Self-care Practices?mentioning
confidence: 99%
“…Bloomquist, Wood, Friedmeyer-Trainor, and Kim (2015) asserted that "a paucity of research exists with regard to social workers' perceptions of self-care" (p. 294). Miller, Lianekhammy, Pope, Lee, and Grise-Owens (2017) reported that there are not as many research studies on self-care as one might expect. Others have made similar assertions (Cox & Steiner, 2013;Grise-Owens, Miller, Escobar-Ratliff, & George, 2017;Lee & Miller, 2013).…”
Section: Social Work Research About Self-carementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in their sample of graduate-level practitioners, Bloomquist et al (2015: 304) found that ‘overall findings suggest that social workers are not frequently practicing self-care’. In examining self-care practices of healthcare social workers, Miller et al (2017) reported that participants only minimally engaged in self-care. Other studies have reached similar conclusions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Radical Self-care for Social Workers 7 Social work is among the highest risk professions for stress, burnout, and job turnover rates (Cox & Steiner, 2013;Miller et al, 2017;Smullens, 2015;Travis, Lizano & Mor Barak, 2016). Studies suggest that social workers experience high reports of stress, burnout, negative views on work and work-based relationships, anxiety, depression, work strain, lack of job satisfaction, and engage in unhealthy coping mechanisms (Nissly, Mor Barak & Levin, 2005;Travis, Lizano & Mor Barak, 2016;Tham, 2007;Tham & Meagher, 2009).…”
mentioning
confidence: 99%